2021
DOI: 10.1016/j.artd.2021.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Hip Arthrodesis Using Robotic Arm Technology

Abstract: Recent advancements in computer-assisted surgery have led to a renewed interest in robotic-assisted hip arthroplasty. This technology assists with component position which is especially useful in prior trauma or dysplasia cases. We present a case of a surgical hip fusion conversion to total hip arthroplasty with the use of robotic-assisted technology. Enhanced preoperative planning with the ability to manipulate implant position before execution can be invaluable during complex procedures. Further research is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Overall, 180 records were excluded for duplicates, 197 records were identified as irrelevant by screening titles and abstracts, and the remaining 16 records were assessed for eligibility by reviewing full-text articles. After applying the inclusion criteria, ten studies were included in the present scoping review ( 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ).
Figure 1 PRISMA flow diagram showing the process of literature screening, study selection, and reasons for exclusion.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 180 records were excluded for duplicates, 197 records were identified as irrelevant by screening titles and abstracts, and the remaining 16 records were assessed for eligibility by reviewing full-text articles. After applying the inclusion criteria, ten studies were included in the present scoping review ( 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ).
Figure 1 PRISMA flow diagram showing the process of literature screening, study selection, and reasons for exclusion.
…”
Section: Resultsmentioning
confidence: 99%
“…Considering that there has been some pioneering work in applying the robotic system in revision TJA (22,23,24,25,26,27,28,29,30,31), and robotic-assisted technology may have more extended applications in the future, we performed a scoping review of the literature and narrative synthesis to present the current state-of-the-art.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total hips, the computer-based software allows the surgeon to individualize the cup inclination/version, thereby decreasing dislocation rates [ 25 ]. Previous studies have shown that the robotic-arm assistance can be used for the conversion of UKA to TKA as well as previous hip fusion to THA [ 12 , 13 ]. To our knowledge, this is the first report of this technology being used for revision of a total knee replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons continue to harness the abilities of robotics and devise ways to use new technology during surgery. There are case reports of the robot being used in the conversion of UKA to TKA, as well as conversion of previous hip fusion to THA [ 12 , 13 ]. Advanced imaging is frequently used for preoperative planning, which can be helpful in the restoration of native anatomy.…”
Section: Introductionmentioning
confidence: 99%